Proceedings of the 24th International Conference on Auditory Display - ICAD 2018 2018
DOI: 10.21785/icad2018.022
|View full text |Cite
|
Sign up to set email alerts
|

Photone: Exploring Modal Synergy in Photographic Images and Music

Abstract: We present Photone, an interactive installation combining photographic images and musical sonification. An image is displayed, and a dynamic musical score is generated based on the overall color properties of the image and the color value of the pixel under the cursor. Hence, the music changes as the user moves the cursor. This simple approach turns out to have interesting experiential qualities in use. The composition of images and music invites the user to explore the combination of hues and textures, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Already in our previous study [1], our conjecture was that only a limited proportion of a general audience would find interacting with Photone engaging beyond the cursory examination and superficial poking. The distribution of the log data in our present work (Figure 4) confirms this conjecture.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Already in our previous study [1], our conjecture was that only a limited proportion of a general audience would find interacting with Photone engaging beyond the cursory examination and superficial poking. The distribution of the log data in our present work (Figure 4) confirms this conjecture.…”
Section: Discussionmentioning
confidence: 88%
“…Superficially, the concept of Photone might be described as musicalization of a visual image, as the interaction incorporates musical aspects into the image making it possible to listen to the music of the colors [20]. However, in Photone image, sound, and interaction are tightly integrated, and we argue that the three elements are aspects of the same emergent experience in use [1].…”
Section: Sonification Music and Imagesmentioning
confidence: 98%
See 2 more Smart Citations
“…Strong associations were also found between music-color mappings and emotions, as different emotions can be evoked through them [16], and the study also found other musical parameters like tempo and mode can play an important yet unclear role. Prior research on photographic sonification has also yielded several sonification methods and algorithms, adhering to a musical approach focused on musical structure [17] or a naturalistic one following viewing tendencies [18]. Additionally, research on visual saliency in paintings has yielded several algorithms that can imitate human gaze perception and fixations, regardless of art movement the visual artwork belongs to [19].…”
Section: Related Workmentioning
confidence: 99%